O abuso de direito de voto nas sociedades anônimas e a possibilidade do voto abusivo minoritário - Azevedo, Guilherme Martiniano de (2024)
The objective of this study is to examine cases of abuse in the exercise of voting rightsby minority shareholders in public limited companies. It begins with a theoreticalanalysis of principles, institutes and concepts essential for a proper understanding ofthe subject, in order to discuss the various situations of abuse by the minority. It alsoinvestigates the practice of surprise voting, where the minority benefits from theabstention of the majority. In addition, it discusses abuse related to the exclusion ofthe majority, often manifested through the undue rejection of accounts and financialstatements, in which directors are unable to vote on deliberations. The researchexamines the various types and purposes of these agreements, seeking to understandthe purpose of each of them within a company and the benefits they provide toshareholders, in addition to the impacts on the company, its managers and thirdparties. Finally, it discusses the misuse of the right to vote and representation on thefiscal and administrative boards, and also presents relevant case studies